A Multicenter Study on Clinical Outcomes of Simultaneous Implantable Collamer Lens Removal and Phacoemulsification with Intraocular Lens Implantation in Eyes Developing Cataract - Kazutaka Kamiya; Kimiya Shimizu; Yoshihiro Kitazawa; Takashi Kojima; Tomoaki Nakamura; Kazuo Ichikawa; Kahoko Fujimoto; the Japan ICL Study Group (Ophthalmology and Therapy)
Abstract Introduction This study evaluated the clinical outcomes of simultaneous implantable collamer lens (ICL) removal and phacoemulsification with intraocular lens (IOL) implantation in a multicenter study. Methods We retrospectively investigated 83 eyes of 72 patients requiring ICL extraction and cataract surgery at five institutions. Preoperatively and 3 months postoperatively, we determined visual acuity (logMAR), spherical equivalent refraction, and endothelial cell density (ECD), in addition to the preoperative backgrounds and the postoperative complications. Results The patients’ age at the time of cataract surgery was 49.8 ± 6.8 years, and the axial length was 28.49 ± 1.97 mm. The most prevalent type of cataract was anterior subcapsular cataract, followed by nuclear and cortical cataract. Uncorrected and corrected visual acuities significantly improved to 0.09 ± 0.30 and − 0.12 ± 0.12 logMAR, respectively (p < 0.001). Sixty-three (76%) and 78 (94%) eyes were within ± 0.5 D and 1.0 D, respectively, of the targeted correction. The mean percentage of ECD loss was 1.3 ± 11.3%. No vision-threatening complications were observed in any case. Conclusions Our multicenter study showed that simultaneous ICL removal and phacoemulsification with IOL implantation is a safe, effective, and predictable procedure, with no significant complications, making it a feasible option for ICL-implanted eyes developing cataracts.